Relating Medical Errors to Medical Specialties: A Mixed Analysis Based on Litigation Documents and Qualitative Data - Liu J; Liu P; Gong X; Liang F (Dove Medical Press, 2020)
Junqiang Liu,1,2 Paicheng Liu,1 Xue Gong,1 Fengbo Liang1 1School of Government, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Center for Chinese Public Administration Research, Sun Yat-sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Junqiang LiuSchool of Government, Sun Yat-sen University, No. 135, Xingang Xi Road, Guangzhou, People’s Republic of ChinaTel +86 20-84111433Email liujq26@mail.sysu.edu.cnPaicheng LiuSchool of Government, Sun Yat-sen University, No. 135, Xingang Xi Road, Guangzhou, People’s Republic of ChinaTel +86 18580008701Email pai_cheng@126.comBackground: We know a great deal about types, causes, and prevention of medical errors, as well as the risks of each medical specialties. Although we know something about medical errors, much remains to be done in this area particularly around effective prevention. However, little is known about whether medical errors are related to medical specialties. Our objective was to categorize and map the distribution of medical errors and analyze their relationships with medical specialties.Methods: First, public cases of medical disputes were searched on “China Judgment Online” according to the key words including medical errors. Second, we set up a database with 5237 medical litigations. After removing unrelated judgment documents, we used systematic random sampling to extract half of these. Then, we hired two frontline physicians with M.D. to review the litigation documents and independently determine the medical errors and the departments in which they took place. A third physician further reviewed the divergent results. After the descriptive statistical analysis and mind map analysis, semi-structured interviews were further conducted with 63 doctors to reveal the relationships mentioned above.Results: More than 97.8% of medical errors occurred in clinical departments. The insufficient implementation of informed consent obligations is the top medical error in all medical departments [internal medical departments (12.86%, N=36), surgical departments (14.57%, N=106), specialist departments (13.16%, N=86)]. The types of medical errors in diverse medical departments might be associated with therapeutic means used by physicians. Errors related to surgical operations were common in surgical departments, errors related to diagnoses were common in internal medicine departments, and errors related to therapy were common in specialist departments. A lack of clinical experience and undesirable work system design have contributed to the occurrence of medical errors. Inadequate human resources and unreasonable shift systems have increased the workload of staff members and this has in turn increased the incidence rate of medical errors.Conclusion: Medical departments are facing medical errors both in humanity and technology. Medical institutions should be alert to the harm caused by medical humanity (mainly including insufficient communication between physicians and patients, insufficient implementation of infringement of informed consent, infringement of patient’s privacy and overtreatment). Improving the clinical skill and vigilance of medical staff is a top priority. Medical institutions should also improve undesirable system designs.Keywords: medical errors, medical specialties, patient safety, medical disputes, China